Expression of Fc-Gamma Receptors of Neutrophils in Preterm Infants of Different Gestational Age - Vladimir E. Mukhin; Daria A. Praulova; Lyudmila L. Pankratyeva; Olga I. Mileva; Alexander G. Rumyantsev; Nikolay N. Volodin (Вопросы современной педиатрии, 2016)
Background: Premature infants have a high risk of bacterial infections facilitated by the immaturity of their immune system.Objective: Our aim was to study the expression of Fc-gamma receptors of neutrophils and the possibility of its modulation in preterm infants (with a low, LBW, very low, VLBW and extremely low, ELBW, birth weight) with bacterial infection.Methods: We examined cord blood samples, as well as peripheral venous blood samples of newborns taken at 28–30th day of life. The flow cytofluorometry method was used to determine the level of surface expression of Fc-gamma receptors by neutrophils (CD64, CD32, CD16), phagocytic activity and oxygen burst of granulocytes stimulated with fluorescently labelled Escherichia coli. Results: We examined blood samples of 10 full-term infants, 20 preterm infants with LBW, 18 preterm infants with VLBW and ELBW. CD64 expression in preterm infants at birth was higher than in full-term children and made 6.0 (5.3; 9.8), 7.1 (5.1; 11.5), and 4.27 (2.4; 5.8) MFI respectively (p = 0.013). CD16 expression in preterm infants, in contrast, was lower: 99.7 (71.3; 126.0) and 80.9 (58.7; 114.8), and 125.3 (95.5; 144.1) MFI respectively (p = 0.021). By the end of the 1st month of life, CD16 expression of peripheral blood neutrophils in preterm infants increased to 126.6 (110.1; 129.0) MFI in children with LBW and to 118.5 (99.5; 132.2) MFI — in children with VLBW/ELBW. CD32 expression in compared groups did not differ. A correlation between the intensity of the oxygen burst of neutrophils and gestational age was established (r = 0.67; p <0.001). Neutrophil culture of preterm infants in the presence of granulocyte colony stimulating factor (G-CSF) results in a 2.4–5-fold increase in CD16, CD32 expression and enhancement of oxygen burst.Conclusion: Preterm infants are characterized by deregulated expression of Fc-gamma receptors and functional impairment of neutrophils. G-CSF modulates the expression of CD16 and CD32 on the surface of neutrophils and enhances the oxygen burst in them.